Clinical effectiveness and cost-effectiveness results from the randomised controlled Trial of Oral Manibular Advancement Devices for Obstructive Sleep apnoea-hypopnoea (TOMADO) and long-term economic analysis of oral devices and continuous positive airway pressure. (October 2014) - Sharples, L
No abstract available